Peculiarities of university brand formation in the context of political branding of the front-line territory (on the example of the city of Kherson) - Serhii Kostiuchkov (Університети і лідерство)
The article substantiates the relevance of the formation and development of the university brand in the context of political branding of the front-line territory, using the example of the city of Kherson, in the conditions of the Russian-Ukrainian war. The role of brands is studied, the creation and promotion of which are urgent tasks for scientists of various fields, as well as for practitioners, since it is brands that are designed to ensure a high level of competitiveness of goods and services in modern markets, in particular - educational services. It has been established that a brand is a product of human imagination and creative activity - it is a kind of mental construct, a mental image, a symbolic model, the activation of which will serve to specify the orientation of the consumer of goods and/or services in the relevant market. The essence of the political brand of the territory, which primarily performs ideological, cultural, patriotic, political and other functions, is revealed. The role of territory branding (geobranding) is shown as a process of brand creation, which aims to promote local, regional and national projects, in particular - political ones, focused on the progressive development of a specific territory; under favorable socio-political conditions, a promising brand will provide an opportunity to effectively invest a regional resource in the political capital of society. Key positions of foreign and domestic researchers regarding the political brand and branding in their constructive connotation are highlighted. The role of unpredictable factors in the development of society is shown, in particular - military actions, which play the role of powerful activators of the process of forming the political branding of a territory or settlement. Emphasized: among the scientific and educational brands of the Kherson region and the regional center, Kherson State University (KSU) occupies a prominent place - a scientific, educational, cultural institution that forms the socio-spiritual and political-economic landscape of southern Ukraine. It is emphasized that during the full-scale invasion of the Russian army on the territory of Ukraine, the brand of Kherson State University acquired new qualitative features, the educational institution became a university of invincible patriots, forming a powerful and bright sub-brand of Kherson - a hero city. It was concluded that the brand of the university, simultaneously with the internal one, demonstrates an external effect aimed at the development of the political brand of a specific territory, actualizing and manifesting feelings of civic cohesion, justice, social responsibility and patriotism.